2010
DOI: 10.1098/rspb.2010.1517
|View full text |Cite
|
Sign up to set email alerts
|

Within and transgenerational immune priming in an insect to a DNA virus

Abstract: Invertebrates mount a sophisticated immune response with the potential to exhibit a form of immune memory through ‘priming’. Increased immune protection following early exposure to bacteria has been found both later in life (within generation priming) and in the next generation (transgeneration priming) in a number of invertebrates. However, it is unclear how general immune priming is and whether immune priming occurs in response to different parasites, including viruses. Here, using Plodia interpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
146
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(152 citation statements)
references
References 41 publications
2
146
1
1
Order By: Relevance
“…We also found that a protective effect of prior treatment with a small dose of the pathogen ('priming') extends for 7 days [previous experiments in this system had only looked for immediate effects and those 2 days following priming exposure (McTaggart et al, 2012)]. This is comparable with the observations of priming after 8 days in beetles (Roth et al, 2009) and 6 days in moths (Tidbury et al, 2011) and shows that priming of the innate system is relatively persistent. This persistent priming also has broad implications for understanding the epidemiological consequences of priming.…”
Section: Research Articlesupporting
confidence: 84%
“…We also found that a protective effect of prior treatment with a small dose of the pathogen ('priming') extends for 7 days [previous experiments in this system had only looked for immediate effects and those 2 days following priming exposure (McTaggart et al, 2012)]. This is comparable with the observations of priming after 8 days in beetles (Roth et al, 2009) and 6 days in moths (Tidbury et al, 2011) and shows that priming of the innate system is relatively persistent. This persistent priming also has broad implications for understanding the epidemiological consequences of priming.…”
Section: Research Articlesupporting
confidence: 84%
“…Because of the trade-off between current egg production and egg protection, TGIP might be expected in iteroparous species rather than in semelparous ones. In line with this, TGIP has been evidenced in iteroparous arthropods [3,4,[9][10][11][12][13][14]35] and not in semelparous ones [36,37]. Iteroparity could allow females to adjust their relative investment into egg protection compared with egg production in accordance to the risk of infection of the progeny and their own risk of dying from the infection.…”
Section: Discussionmentioning
confidence: 81%
“…Similar long-term beneficial effects have also been described for maternal antibodies, which induce T-celldependent idiotypic responses during the neonatal period (3). In addition, transgenerational immune priming has been demonstrated in insects challenged with bacteria or viruses (37,38). Maternally transmitted susceptibility for trypanosome infections has also been described in tsetse (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%